2015
DOI: 10.1371/journal.pone.0136102
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis Surface Cysteine Proteases Induce Cleavage of the Intestinal Epithelial Cytoskeletal Protein Villin via Myosin Light Chain Kinase

Abstract: Giardia duodenalis infections are among the most common causes of waterborne diarrhoeal disease worldwide. At the height of infection, G. duodenalis trophozoites induce multiple pathophysiological processes within intestinal epithelial cells that contribute to the development of diarrhoeal disease. To date, our understanding of pathophysiological processes in giardiasis remains incompletely understood. The present study reveals a previously unappreciated role for G. duodenalis cathepsin cysteine proteases in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 91 publications
(122 reference statements)
2
46
0
Order By: Relevance
“…The formation of the 6 paralogs of genome GSB within clades 7, 8 and 9 can also be caused by selection, because it is known that substrate specificity varies between the paralogs and orthologs of the cathepsins of Giardia . Recombinants of 3 paralogs of cathepsins from GL50803 (Liu et al 2018), but also orthologs of GL50803 and GL50581 (Bhargava et al 2015, Cotton et al 2014) showed differences in substrate specificity. Therefore, the presence of more cathepsin variants within an assemblage, might help to make a less restricted host repertoire possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the 6 paralogs of genome GSB within clades 7, 8 and 9 can also be caused by selection, because it is known that substrate specificity varies between the paralogs and orthologs of the cathepsins of Giardia . Recombinants of 3 paralogs of cathepsins from GL50803 (Liu et al 2018), but also orthologs of GL50803 and GL50581 (Bhargava et al 2015, Cotton et al 2014) showed differences in substrate specificity. Therefore, the presence of more cathepsin variants within an assemblage, might help to make a less restricted host repertoire possible.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant proteins in both isolates were variant-specific surface proteins (VSPs), cathepsins, high cysteine membrane proteins and tenacins. Differences in proteolytic activity and specificity of the cathepsin paralogs and orthologs of different isolates/assemblages have been described (Bhargava et al 2015; Lui et al 2018). So far, nothing is known about the cathepsins of the assemblages of the dog.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Second, Giardia cathepsin B-like proteases induce myosin light chain kinase (MLCK)-mediated villin breakdown and contribute to Giardia-induced microbiota toxicity. 26,27 Findings from other reports suggest that soluble factors secreted by colonic epithelial cell lines are sufficient to up-regulate trophozoite membranous and secreted proteins, such as cathepsin-B precursors, cystatin and VSPs, independent of direct parasite attachment. 20,26 Despite very few virulence factors have been identified and characterized in Giardia to date, an unknown 58-kDa product released by Giardia trophozoites has also been reported to induce physiologic changes at mucosal surface.…”
Section: Parasitic and Host Factors During Giardia-host Cell Interactionmentioning
confidence: 99%
“…26,27 Findings from other reports suggest that soluble factors secreted by colonic epithelial cell lines are sufficient to up-regulate trophozoite membranous and secreted proteins, such as cathepsin-B precursors, cystatin and VSPs, independent of direct parasite attachment. 20,26 Despite very few virulence factors have been identified and characterized in Giardia to date, an unknown 58-kDa product released by Giardia trophozoites has also been reported to induce physiologic changes at mucosal surface. In particular, this factor activates signal transduction pathways in enterocytes leading to anion hypersecretion and intestinal fluid accumulation.…”
Section: Parasitic and Host Factors During Giardia-host Cell Interactionmentioning
confidence: 99%
See 1 more Smart Citation